« Che l’uomo ritorni all’uomo » : la revue Latitudine et l’engagement des intellectuels napolitains d’après-guerre - Virginie Vallet (Laboratoire Italien)
The year 1945 in Naples is marked by a crisis of intellectuals that extends to Europe. After twenty years of cultural obscurantism and empty rhetoric, a new concept of a culture inspired by humanism, with un ritorno dell’uomo all’uomo as a primordial value, oriented towards Europe and the world, is proposed to readers of Latitudine, the pioneering cultural review of the immediate post-war period, directed by Massimo Caprara, the first and only issue of which was published in Naples on January 1944. The civil commitment of ragazzi di Monte Di Dio, young intellectuals who wanted to take concrete action on the history of Naples, a real political and cultural laboratory, is however difficult to dissociate from their complex cultural and ideological background. To what extent can the politicization of cultural life allow the words of the committed intellectual to be interpreted as an objective testimony of a historical period and its zeitgeist ? This article proposes to present this rare issue of Latitudine and to analyse the value of the testimony of the engaged intellectual as a reconstruction of an individual and collective historical memory.